Applicability of Moyers' and Tanaka-Johnston's mixed dentition analyses for predicting canine and premolar widths in south Indian population - A cross sectional study - Rekhalakshmi Kamatham; Kalasandhya Vanjari; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2017)
Aim: To test the applicability of Moyers' and Tanaka-Johnston's (TJ) mixed dentition analyses in predicting canines (C) and premolars (Ps) dimensions in South Indian population. Materials and Methods: A total of 100 boys and 101 girls in the age range of 11-15 years were recruited into the study. Maxillary and mandibular arch impressions were made and poured with dental stone. The maximum mesio-distal widths of mandibular central and lateral incisors, maxillary and mandibular C and Ps were measured. The predicted values of C and Ps obtained using Moyers' and TJ methods were correlated and compared with the actual tooth sizes using Pearson correlation test and paired t test, respectively. Results: Moderate positive correlations were observed between the actual measurements and the predicted values obtained using both TJ and Moyers' methods, irrespective of the gender. However, the validity, as tested using paired t test showed no applicability of TJ and Moyers' (35 and 75%) methods. On the other hand, Moyers' 50% was applicable for both the arches in boys and 65% for girls only in the maxillary arch. Conclusion: TJ and Moyers' methods cannot be applied in the present population (Southeast India); hence, population adjusted regression equations have to be formulated.